Pengukuran Indeks Pertanian Berkelanjutan di Kabupaten Ngawi - Setiawan, Rofi Arif; Baga, Lukman Mohammad; Nurmalina, Rita (Universitas Galuh, 2025)
Sustainable agriculture is a program of the Ngawi Regency Government to increase the agricultural sector’s contribution to the regional economy and provide an alternative for farmers in cultivating rice. Evaluation of this program is carried out partially according to the indicators and targets set. The study aims to measure the sustainability of agriculture through indicators related to the economic, social, and environmental dimensions in conditions before and after the sustainable agriculture program. Measurements are carried out using composite indicators of sustainable agriculture with stages of indicator selection, data gathering, normalization, weighting, and aggregation of indicators. Data before the program was chosen from 2017 to 2020 and after the program was selected from 2021 to 2023. The sustainable agriculture index before the program was 0.48 with a fairly sustainable category. Then the index after the sustainable agriculture program was 0.63 with a sustainable category. Increases occurred in all dimensions indicating the success of the sustainable agriculture program.